Light Beneath a Canopy (First Movement) - Ward, Isaac (My University, 2015)
Premiere performance of a composition for brass ensemble by ECU student composer Isaac Ward. Recorded at A.J. Fletcher Recital Hall on April 20th, 2015
Ben Reyes, Henry Goodwin, trumpets; Payton Chadwick, Emma Johnson, Cameron Elliott, Tayler Goodwin, horns; Preston Ridgell, Josh Bishop, trombones; C.J. Luke, bass trombone; Steven Kosch, euphonium; Zach Grass, tuba
Keywords: Brass ensembles